Molecular Interatcions : The Multipole Expansion - Fernández, Francisco Marcelo (2012)
This laboratory provides students with the opportunity to reinforce their knowledge of the numerous parameters involved in electrophilic aromatic substitution reactions. These concepts are investigated using a benchtop GC-MS. Students obtain hands-on experience with the coupling of gas-chromatographic analysis and mass-spectral analysis. Each student determines one data point by reacting a pair of compounds with bromine and iron (III) chloride. Individual results are then pooled into composite class data, affording students more available information for analysis than is typical in an organic chemistry laboratory.